2018
DOI: 10.1111/jeb.13282
|View full text |Cite
|
Sign up to set email alerts
|

Mutation accumulation in populations of varying size: large effect mutations cause most mutational decline in the rotifer Brachionus calyciflorus under UV‐C radiation

Abstract: Theory predicts that fitness decline via mutation accumulation will depend on population size, but there are only a few direct tests of this key idea. To gain a qualitative understanding of the fitness effect of new mutations, we performed a mutation accumulation experiment with the facultative sexual rotifer Brachionus calyciflorus at six different population sizes under UV-C radiation. Lifetime reproduction assays conducted after ten and sixteen UV-C radiations showed that while small populations lost fitnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
(89 reference statements)
0
9
0
Order By: Relevance
“…(D) A lower base substitution rate in cores relative to arms and tips applies to exons, introns, and intergenic regions. Heilbron et al 2014;Luijckx et al 2018). Although the K a /K s ratio for different population sizes trends in the expected direction, this negative correlation was not significant.…”
Section: Discussionmentioning
confidence: 77%
“…(D) A lower base substitution rate in cores relative to arms and tips applies to exons, introns, and intergenic regions. Heilbron et al 2014;Luijckx et al 2018). Although the K a /K s ratio for different population sizes trends in the expected direction, this negative correlation was not significant.…”
Section: Discussionmentioning
confidence: 77%
“…Over the past few decades, it has been well demonstrated that nature ultraviolet-B (UV-B) radiation increased signi cantly with the continuing depletion of stratospherico zone, which has becoming one of the grave concerns and most striking global changes [10,11]. There is growing evidence that adverse biological effects of ambient ultraviolet radiation exposure occur in not only marine but also freshwater ecosystem at different trophic levels [11,12], involving algae [13], rotifers [14,15], copepods [16,17], cladocerans [18], shrimps [19,20] and shes [21]. In all cases, UVR was found to harm the organisms in question by damaging DNA directly at the molecular level and affect tness at the individual and population levels [22].…”
mentioning
confidence: 99%
“…Similar results have been obtained for other studies in nematode (e.g., K atju et al . 2015) and rotifers (L uijckx et al . 2018), suggesting preponderance of mutations with large fitness effects.…”
Section: Discussionmentioning
confidence: 99%
“…The fate of a new mutation is determined by drift when its fitness effect is less than 1/2Ne (WRIGHT 1931;KIMURA 1983). Empirical evidence suggests that population sizes as low as ten may be sufficient to prevent fixation of mutations with deleterious fitness effects (ESTES et al 2004;KATJU et al 2015;LUIJCKX et al 2018). We imposed a minimum population size of 12 males and 12 females (Figure 2A).…”
Section: Commmentioning
confidence: 99%
See 1 more Smart Citation